an OPERKULEKTOMI PADA PASIEN YANG MEMILIKI REFLEKS MUNTAH TINGGI: LAPORAN KASUS - Chaerita Maulani; Riski Putri Noviani (YARSI Dental Scientific Meeting - e Journal, 2025)
Introduction: The gag reflex is one of the complicating factors that is quite influential on the success of dental treatment, one of which is in the treatment of dentists in patients with partially erupted third molars. Case Report: A 22-year-old female patient came with a complaint of wanting to clean tartar. The patient also complained that the lower right back tooth was often stuck with food and was difficult to clean because it was covered by the gums. The patient had no systemic disease, had no drug and food allergies, and did not smoke. This patient during examination was found to have a high gag reflex, so special measures were needed to overcome this problem. Discussion: Patients with low and moderate gag reflex can be handled easily during treatment, but patients with high gag reflex require special handling. Handling of patients who have a high gag reflex can use several methods including breath control and distraction during treatment. Conclusion: In dental treatment, excessive gag reflex can interfere with the patient and the dentist's work process which causes the patient to worry every time they visit the dentist. The method of managing the gag reflex can be done so that a comfortable and productive treatment can be obtained.